Strategi Meningkatkan Keterampilan Berbicara Peserta Didik Kelas V Sekolah Dasar Melalui Peningkatan Kecerdasan Interpersonal dan Kepercayaan Diri - Rima Rahmawati; Gusti Yarmi; Lidwina Sri Ardiasih (SAP (Susunan Artikel Pendidikan), 2021)
As an attempt to improve the quality of education in Indonesia, this study aims to analyze the correlation between interpersonal intelligence (X1) and self-confidence (X2) on the students speaking skills (Y) in grade V elementary school. This study occupied a quantitative approach with correlational techniques. The sample in this study amounted to 105 people. The sample was determined using the random cluster technique. The entire data collection process was carried out before the COVID-19 pandemic, from October to December 2019. From the analysis, it was found that there was a significant positive correlation between interpersonal intelligence and speaking skills with an effective contribution of 44%, and there was a significant positive correlation between self-confidence in speaking skills and an effective contribution of 55.4%. Simultaneously, both of them have a significant positive correlation towards the speaking skills of grade V students. Practically, from this research, teachers are expected to be able to make observations and to improve interpersonal intelligence and self-confidence of students as an effort to improve students' speaking skills.